DBASE III PLUS APPLICATIONS IN SALES PANTILE XYZ - Muhammad Mekah Madinarovah; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2000)
With existence of computerized sales system, then the expected improvements in the sales field because in this system can facilitate in providing necessary information on matters relating to the sale, helping to reduce errors in routine work and easy to provide reports in complete and correct at any time the report was required.